Upaya Meningkatkan Minat Belajar Murid Melalui Pembelajaran Berdiferensiasi dengan Model Pembelajaran Problem Based Learning pada Pelajaran IPS - Sumarni, Enny (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2023)
Classroom Action Research (CAR) was carried out for three months from September 2022 to November 2022, with two cycles and four stages in each cycle, namely: 1) planning; 2) implementation; 3) observation; and 4) reflection. The background for preparing this research report is due to implementation problems. Differentiated learning with the Problem Based Learning (PBL) learning model, in the Implementation of Independent Curriculum Learning in class VII which has just been implemented at SMP Negeri 2 Telukjambe Timur, Karawang Regency, West Java Province since the beginning of the 2022/2023 school year. The purpose of this study was to increase students' interest in learning in class VII.G in social studies through differentiated learning using the Problem Based Learning (PBL) learning model. The results of this study showed that the average student learning interest increased by 0.8 points, the average individual formative assessment results increased by 21 points, and the average group work results increased by 14 points. In conclusion, this study "succeeded" in increasing students' interest in learning through differentiated learning with the Problem Based Learning (PBL) learning model in social studies lessons in Class VII.G of SMP Negeri 2 Telukjambe Timur.